2020
DOI: 10.1109/access.2020.3034833
|View full text |Cite
|
Sign up to set email alerts
|

Metasurface Matching Layers for Enhanced Electric Field Penetration Into the Human Body

Abstract: The use of electromagnetic fields applied to human tissues has proven to be beneficial in several applications, such as monitoring physiological parameters and delivering medical treatments. Often applications rely on targeted energy deposition into the tissue, or rely on wireless powering of implanted devices. In such cases, the system energy efficiency, the stability of the field, and ultimately the process safety could all benefit from minimizing the mismatch at the air-skin interface. In this paper, the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 45 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…In [138], authors describe an electrically small antenna employing an AMC substrate, both fabricated by using an inkjet-printed solution, for sub-GHz applications. In another case [139], the use of metamaterials is explored to improve the penetration of the electric field inside the human body for diagnostic/therapy applications. The work addresses the problem of designing a thin matching layer based on a metasurface to increase the electric field penetration into muscle tissue for various scenarios.…”
Section: Emerging Materials For Wearablesmentioning
confidence: 99%
“…In [138], authors describe an electrically small antenna employing an AMC substrate, both fabricated by using an inkjet-printed solution, for sub-GHz applications. In another case [139], the use of metamaterials is explored to improve the penetration of the electric field inside the human body for diagnostic/therapy applications. The work addresses the problem of designing a thin matching layer based on a metasurface to increase the electric field penetration into muscle tissue for various scenarios.…”
Section: Emerging Materials For Wearablesmentioning
confidence: 99%
“…In a recent study, this issue is addressed by introducing a chest-wearable 60 GHz radar system for continuous monitoring of cardiorespiratory displacement waveforms, evaluating the antenna’s performance in close proximity to the skin with an air gap of λ using electromagnetic simulations 20 . Placing an appropriate solid or liquid media between the antenna and the tissue is another approach to effectively reduce antenna mismatching 43 . To mitigate impedance mismatch, however, a number of media layers are required, resulting in a high-profile structure that poses integration difficulties, and applying liquid onto a person’s skin can evoke discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, a huge effort in the literature has been directed to address this specific aspect and several technological solutions have been suggested so far. In particular, it has been demonstrated that interposing appropriate media (solid or liquids) between the antenna and the tissue can alleviate the mismatching issues [27]. Nevertheless, such solutions are generally cumbersome and they cannot be easily applied, especially for wearable and medical devices [28].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, such solutions are generally cumbersome and they cannot be easily applied, especially for wearable and medical devices [28]. Indeed, very often several layers of media are required to mitigate the impedance mismatch at the air-tissue interface [27]. To overcome such limitation, also metamaterials and metasurfaces have been proposed to relieve the tissue effects on the radiating elements.…”
Section: Introductionmentioning
confidence: 99%